Examining the Unanticipated Adverse Consequences of Youth Suicide Prevention Strategies: A Literature Review with Recommendations for Prevention Programs. Issue 4 (12th July 2018) - Kuiper, Nora; Goldston, David; Godoy Garraza, Lucas; Walrath, Christine; Gould, Madelyn; McKeon, Richard
Abstract : Objective: Youth suicide is a public health problem in the United States. Suicide prevention programs have been shown to be beneficial; however, knowledge of unanticipated adverse consequences of programs is limited. The objective of this review is to present what is known about these consequences so informed decisions and appropriate planning can be made prior to implementation of suicide prevention interventions. Method: A narrative but systematic review was conducted assessing what is known about adverse consequences utilizing a comprehensive keyword search of EBSCO and PubMed databases. Study populations beyond youth were included. Results: Unanticipated adverse consequences of suicide prevention interventions were included in 22 publications. Consequences occur at three levels: at the level of the youth, those who identify or intervene with at‐risk youth, and at the system level. While rare, unanticipated adverse consequences include an increase in maladaptive coping and a decrease in help‐seeking among program targets, overburden or increased suicide ideation among program implementers, and inadequate systemic preparedness. Conclusions: Overall, the benefits of youth suicide prevention outweigh the unanticipated adverse consequences. Nevertheless, these results may be utilized for informed decision‐making regarding suicide prevention programming, and to ensure appropriate infrastructure is in place prior to prevention efforts.